1993
DOI: 10.2134/agronj1993.00021962008500060014x
|View full text |Cite
|
Sign up to set email alerts
|

Grain Yield of Subsurface Microirrigated Corn as Affected by Irrigation Line Spacing

Abstract: Without irrigation, crop yields are usually water‐limited on the acid soils of the southeastern USA. Economically feasible irrigation systems that require less water are needed. As part of a feasibility study of subsurface microirrigation for corn (Zea mays L.) production, the effects of irrigation line spacing and irrigation water amount were investigated in a 5‐yr study at Suffolk, VA. The soil was a Uchee loamy sand (loamy, siliceous, thermic Arenic Hapludult) with inclusions of Emporia loamy sand (fine‐loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 7 publications
2
25
0
3
Order By: Relevance
“…The 2-m lateral spacing had a higher slope, indicating a greater decrease in ear weight with distance from the SDI lateral. Ear length and weight results were similar to the normalized corn grain yields for those observed by Powell and Wright (1993). In a 4-year study, they found decreasing corn yields with increasing distance from the SDI laterals.…”
Section: Distance From Sdi Lateral Impacts On Biomass Nitrogen and supporting
confidence: 74%
See 1 more Smart Citation
“…The 2-m lateral spacing had a higher slope, indicating a greater decrease in ear weight with distance from the SDI lateral. Ear length and weight results were similar to the normalized corn grain yields for those observed by Powell and Wright (1993). In a 4-year study, they found decreasing corn yields with increasing distance from the SDI laterals.…”
Section: Distance From Sdi Lateral Impacts On Biomass Nitrogen and supporting
confidence: 74%
“…In Virginia, Powell and Wright (1993) evaluated corn yields on a loamy sand soil using SDI spacings of 0.91, 1.83, and 2.74 m. They found that additional irrigation was required for the wider lateral spacing to obtain corn yields comparable to the narrow lateral spacings. The highest observed yields were from the narrow SDI laterals that were under each corn row.…”
mentioning
confidence: 99%
“…Subsurface drip systems are adaptable to variations of field shape making them an important consideration in the Southeast. In recent years, drip irrigation has been expanded with good success on field crops such as corn (Zea mays L.) (Lamm et al, 1997(Lamm et al, , 2001Mitchell, 1981;Mitchell and Sparks, 1982;Powell and Wright, 1993), cotton (Gossypium hirsutum L.) (Camp et al 1997;Sorensen et al, 2004), and peanut (Jordan et al, 2002;Sorensen et al, 2001a, b;Zhu et al, 2004). Irrigation SDI laterals have been installed at 0.2 and 0.3 m soil depths (Bucks et al, 1981;Camp et al, 1989;Phene et al, 1987;Tollefson, 1985) on cotton, corn, fruits, and vegetables.…”
mentioning
confidence: 99%
“…However, the 2.0 m dripline spacing still increased the yield over rainfed production by 18%. Average corn yields were 100%, 93%, and 94% of the maximum yield for dripline spacings of 0.91, 1.83, and 2.74 m in the humid region of Virginia under adequate irrigation on a loamy sand (Powell and Wright, 1993). In an economic comparison of these results, it was concluded that the 1.8 m spacing was best for corn and peanut rotations (Bosch et al, 1998) in Virginia and North Carolina.…”
Section: Dripline Spacing For Cornmentioning
confidence: 96%